Design Of Teaching Tools For Spatial Ability In Stuffed Space Building Materials - Damayanti, Asri (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
The low mathematical ability of students in spatial geometry material is due, in part, to the low spatial abilities of students, so the researcher designed a learning media in the form of a betel prop. This study aims to produce a design for the development of tepak betel teaching aids for students' spatial abilities in truncated geometric shapes. This research is a development (RnD) using a 4-D development model which is modified into 3-D namely the define stage, the design stage, and the develop stage. The research instrument was an expert feasibility test questionnaire and an instrument for evaluating learning outcomes. Based on the results of the expert validation, the results of the final assessment on IPPP-1 by the three experts with an average score of 3.72 with a percentage of 93.0% met the eligibility criteria. The results of the final assessment on IPPP-2 by the three experts with an average score of 3.83 with a percentage of 95.8% met the feasible criteria. As well as the results of the final IPPP-3 assessment by the three experts with an average score of 3.69 with a percentage of 92.4% meeting the feasible criteria. Based on these data, it can be concluded that the design of the tepak sirih teaching aid development on students' spatial abilities in the material of truncated geometric shapes is feasible to use.Keywords: Design Development, Props, Tepak Sirih